2022
DOI: 10.3389/fneur.2021.799002
|View full text |Cite
|
Sign up to set email alerts
|

New Anti-CGRP Medications in the Treatment of Vestibular Migraine

Abstract: BackgroundVestibular migraine (VM) is a condition associated with migraine headache, vertigo, dizziness, and balance disturbances. Treatment options are limited. It is unknown if new calcitonin gene-related peptide (CGRP) migraine medications have efficacy in treating VM.MethodsWe retrospectively reviewed all patients with VM who were prescribed one of the new CGRP medications between January 2016 and July 2020. In total, 28 patients met the inclusion criteria. We specifically evaluated the “older” CGRP medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…Clinical studies on effectiveness of CGRP monoclonal antibodies are underway for VM, using the newly developed VM-PATHI instrument to score outcome measures (Sharon JD et al, 2020). A recent case review has found that 60% of patients with VM have their VM symptoms moderately relieved with CGRP signaling blockers (Hoskin JL and Fife TD, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies on effectiveness of CGRP monoclonal antibodies are underway for VM, using the newly developed VM-PATHI instrument to score outcome measures (Sharon JD et al, 2020). A recent case review has found that 60% of patients with VM have their VM symptoms moderately relieved with CGRP signaling blockers (Hoskin JL and Fife TD, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…8 Current research suggests that a change in ion channel function results in altered neural activity in the trigeminovascular system, which results in release of neurotransmitters such as substance P and calcitonin gene-receptor peptide (CGRP). 9 Receptors for CGRP are expressed in the vestibular system and have been associated with motion sickness. 9 Activation of this system likely is a contributing factor for the pathophysiology of vestibular migraine.…”
Section: Pathophysiologymentioning
confidence: 99%
“…3,8 The most frequent vertigo symptoms in vestibular migraine are spontaneous rotatory vertigo and positional vertigo but patients also may experience visually induced vertigo and head motion-induced vertigo. 3,9 Patients are most likely to describe a sense of spinning, fl oating, rocking, tilting, swaying, feeling off-balance, lightheaded, or foggy. 1 Vestibular symptoms are often triggered or aggravated by changing position, movement, or visual motion within the patient's environment.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations